Anaphylaxis Associated With Allergen Specific Immunotherapy, Omalizumab, and Dupilumab: A Real World Study Based on the US Food and Drug Administration Adverse Event Reporting System - Bian, Sainan; Zhang, Pingping; Li, Lisha; Wang, Zixi; Cui, Le; Xu, Yingyang; Guan, Kai; Zhao, Bin; Chen, Zhuanggui (Frontiers in Pharmacology, 2021)
Background: Real-world studies on the allergen specific immunotherapy (AIT), omalizumab, and dupilumab associated anaphylactic events are limited. We aimed to analyze the characteristics of drug associated anaphylaxis, and to compare the differences among different drugs. Methods: A disproportionality analysis and Bayesian analysis were used in data mining to identify suspected anaphylaxis associated with AIT, omalizumab, and dupilumab based on the Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) from January 2004 to March 2021. Demographic information, time interval to onset, and death rates of AIT, omalizumab, and dupilumab associated anaphylaxis were also analyzed. Results: Totally 9 969 anaphylactic events were identified. Reports of AIT, omalizumab, and dupilumab associated anaphylactic events were 64, 7 784, and 2 121, respectively. AIT had a high reporting odds ratio (ROR) of 5.03(95%confidental interval 3.69-6.85), followed by omalizumab (ROR 2.24, 95%CI 2.18-2.29), and dupilumab had a negative signal for anaphylaxis. In children, most anaphylactic reactions (68%) were reported in the 12 to 17-year-old group. More reports of anaphylaxis related to AIT were in boys (73%), while more reports of anaphylaxis related to omalizumab (63%) and dupilumab (58%) were in girls. Most symptoms occurred on the day of drug initiation. The death rate of AIT related anaphylaxis was the lowest (0%), the death rate of omalizumab was 0.87%, while the death rate of dupilumab was 4.76%. No significant differences were observed among these drugs. Conclusions: AIT and omalizumab had a positive signal for anaphylaxis, while dupilumab had a negative ROR for anaphylaxis. Patients should be strictly monitored after administration of AIT and also biologics. It also gives us a suggestion for choosing a combined biologics with AIT when the risk of anaphylaxis was considered.